2004
DOI: 10.1111/j.1439-0418.2004.00858
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA variation in Spanish populations of Ceratitis capitata (Wiedemann) (Tephritidae) and the colonization process

Abstract: Mitochondrial DNA variation in the Mediterranean fruit fly Ceratitis capitata (Wiedemann, Diptera: Tephritidae) was studied in three natural populations from southern, central and eastern Spain by means of restriction fragment length polymorphisms using 22 restriction endonucleases. Nine different haplotypes were found based upon the restriction patterns of the seven polymorphic endonucleases, providing a measure of discrimination between populations (N ST ¼ 0.2462, F ST ¼ 0.154). The observed distribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
(64 reference statements)
3
9
0
Order By: Relevance
“…Overall, the number of haplotypes uncovered here confi rms the high level of variability in the populations of this pest within Tunisia. Th is consistent with the idea that the Tunisian populations, which are "ancient" by medfl y standards , are expected to be more diverse than populations recently established (Reyes and Ochando 2004). Previous studies had shown that the fi rst major expansion of this pest into non native areas included countries of the Mediterranean basin ), but quantifi cation of the level of variability in these populations had remained elusive when populations, such as those from Tunisia, proved to be diffi cult to analysis using the PCR-RFLP approach (Gasparich et al 1997).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Overall, the number of haplotypes uncovered here confi rms the high level of variability in the populations of this pest within Tunisia. Th is consistent with the idea that the Tunisian populations, which are "ancient" by medfl y standards , are expected to be more diverse than populations recently established (Reyes and Ochando 2004). Previous studies had shown that the fi rst major expansion of this pest into non native areas included countries of the Mediterranean basin ), but quantifi cation of the level of variability in these populations had remained elusive when populations, such as those from Tunisia, proved to be diffi cult to analysis using the PCR-RFLP approach (Gasparich et al 1997).…”
Section: Discussionsupporting
confidence: 75%
“…DNA markers used in previous studies of Mediterranean fruit fl y populations include those derived from nuclear genes such as RAPDs (Haymer & McInnis 1994) and intron sequences He & Haymer 1999), microsatellites (Bonizzoni et al 2001), as well as those derived from mitochondrial DNA (mtDNA) (McPheron et al 1994;Gasparich et al 1995;Kourti 1997;Ochando et al 2003). Mitochondrial DNA markers in particular have proved to be effi cient for characterizing some aspects of the genetic diversity of medfl y populations due in part to its haploid and uniparental (maternal) mode of inheritance and to the absence of recombination (Reyes & Ochando 2004). However, mitochondrial DNA studies have relied on the use of a PCR-RFLP method to identify diagnostic restriction site polymorphisms (McPheron et al 1994) in genes such as the ND4 (NADH subunit 4) and ND5 (NADH subunit 5) genes (Sheppard et al 1992;Gasparich et al 1995;Meixner et al 2002).…”
mentioning
confidence: 99%
“…The polymorphism, considering both markers simultaneously, varied between the 0.96 for the population from Morocco to the 0.72 for the population from Brazil, which reflects the African origin of this species and the recent colonization of South America Barr, 2009). Mediterranean Spanish populations showed intermediate levels of polymorphism, as reported in other studies including Mediterranean basin populations Reyes & Ochando, 1998, 2004. When a dendrogram based on Nei genetic distances was constructed using simultaneously both kinds of markers, all Mediterranean Spanish populations, except the population collected in Gerona, were clearly differentiated from the rest.…”
Section: Patterns Of Distribution Of the Genetic Variabilitysupporting
confidence: 54%
“…Over the last two decades several works have attempted to determine the genetic structure of medfly populations at different geographical scales, as well as to resolve more exactly the possible colonization pathways using these methodologies (e.g. Baruffi et al, 1995;Malacrida et al, 1998;He & Haymer, 1999;Ochando et al, 2003;Reyes & Ochando, 2004;Barr, 2009;Alaoui et al, 2010). Regarding medfly Spanish populations, our studies revealed high Genetic structure of Ceratitis capitata Spanish Mediterranean area (Gerona, Amposta, Tortosa, Castellón, Valencia and Málaga), two from Atlantic Islands (Tenerife and Madeira) and three from other geographical regions (Morocco, Israel and Brazil).…”
Section: Introductionmentioning
confidence: 99%
“…This is due to some of its peculiarities, such as strictly maternal inheritance, absence of recombination, a relatively high mutation rate, and, last but not least, the availability of efficient PCR primers (Simon et al 1994) and a wealth of comparative data (Boykin et al 2006;Mun et al 2003;Shi et al 2005;Nardi et al 2003Nardi et al , 2005Jamnongluk et al 2003;Reyes and Ochando 2004;Xie et al 2006). Mitochondrial cytochrome oxidase subunit I (COI) sequences were shown to be appropriate for intraspecific analysis because of the high degree of polymorphism observed.…”
Section: Introductionmentioning
confidence: 97%